Influence of H₂S Corrosion on Tensile Properties and Fracture Toughness of X80 Pipeline Steel - Gu, L.; Wang, J.; Luan, C.B. (Проблемы прочности, 2019)
Tensile and fracture properties of X80 pipeline steel were studied in a mimic petrochemical environment. X80 pipeline steel specimens were firstly exposed to air or H₂S corrosive medium. Then their tensile properties and δ-Δa resistance curves were obtained in experiments. The influence of H₂S corrosion on the X80 pipeline steel’s crack growth resistance curve, fracture toughness, and plastic work loss was analyzed. The comparison between the test results after two pretreatments indicates that there was no significant difference in the X80 pipeline steel’s ultimate tensile strength before and after H₂S corrosion. But fracture elongation, area reduction and fracture toughness varied greatly (a substantial decrease in elongation and reduction of area). The crack growth resistance curve of the specimen in air was obviously higher than the crack growth resistance curve of the corroded one. Under stable crack growth stage, the crack initiation toughness δ0.2BL of the specimen in air was 0.732 mm, 2.02 times that of the corroded one (0.364 mm). In the case of similar crack growth Δa, the plastic work required in the crack growing process (Uр ) of the specimen in air was 2.29 times that of the H₂S-corroded specimen (U'р). H₂S corrosion resulted in a significant reduction of the fracture toughness of X80 pipeline steel. Hence, H₂S corrosion should be avoided in the process of natural gas transportation by pipelines, so as to protect the pipeline steel from toughness degradation. Исследованы прочность при растяжении и вязкость разрушения трубопроводной стали Х80 в среде, характерной для нефтехимических процессов. Образцы стали подвергали длительному воздействию воздуха и коррозионной среды, содержащей сероводород, а затем испытывали на растяжение и трещиностойкость при трехточечном изгибе с построением кривых напряжение деформация и раскрытие трещины в ее вершине длина трещины. Выполнен анализ влияния сероводородной коррозии на диаграмму роста трещины, вязкость разрушения и работу пластической деформации. Анализ результатов, полученных на образцах в исходном состоянии и подвергнутых воздействию сероводородной среды, показал, что данный фактор незначительно снижает предел прочности стали при растяжении, однако приводит к существенному удлинению, а также к уменьшению сечения образцов при разрушении и вязкости разрушения. На стадии устойчивого роста трещины раскрытие ее вершины при страгивании на воздухе составляло 0,732 мм, что более чем вдвое выше, чем в коррозионной среде (0,364 мм). При этом работа пластической деформации, необходимая для продвижения трещины на одну и ту же длину Δa, при воздействии воздуха в 2,29 раза выше, чем коррозионной среды. При транспортировке природного газа по трубопроводам следует избегать коррозионного воздействия сероводорода, существенно снижающего вязкость разрушения трубопроводной стали. Досліджено міцність при розтягуванні і в'язкість руйнування трубопровідної стали Х80 в середовищі, характерної для нафтохімічних процесів. Зразки стали піддавали тривалому впливу повітря і корозійного середовища, що містить сірководень, а потім випробовували на розтягнення і тріщиностійкість при трьохточкову згинанні з побудовою кривих напруга-деформація і розкриття тріщини в її вершині-довжина тріщини. Виконано аналіз впливу сірководневої корозії на діаграму зростання тріщини, в'язкість руйнування і роботу пластичної деформації. Аналіз результатів, отриманих на зразках в початковому стані і підданих впливу сірководневої середовища, показав, що даний фактор тільки незначною мірою зменшує межу міцності стали при розтягуванні, проте призводить до істотного подовження, а також до зменшення перетину зразків при руйнуванні і в'язкості руйнування. На стадії стійкого росту тріщини розкриття її вершини при зсуві на повітрі становило 0,732 мм, що більш ніж удвічі вище, ніж в корозійної середовищі (0,364 мм). При цьому робота пластичної деформації, необхідна для просування тріщини на одну і ту ж довжину, при впливі повітря в 2,29 рази вище, ніж корозійного середовища. При транспортуванні природного газу по трубопроводах слід уникати корозійного впливу сірководню, що істотно знижує в'язкість руйнування трубопровідної сталі.